The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.2044-8260.1997.tb01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective processing of shape‐related words in women with eating disorders, and those who have recovered

Abstract: The results suggest that there may be an enduring cognitive bias among women who have recovered from anorexia. This is the first study in which impairment on an emotional Stroop task has been found to persist after recovery from a clinical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 10 publications
0
32
2
2
Order By: Relevance
“…Prospective studies have found overconcern with weight and shape to be predictive of problematic eating behavior (Button, Sonuga-Barke, Davies, & Thompson, 1996;Graber, Brooks-Gunn, Paikoff, & Warren, 1994;Killen et al, 1994Killen et al, , 1996; experimental studies have demonstrated that eating disorder patients selectively attend to weight and shape-related information (Ben-Tovim & Walker, 1991;Ben-Tovim, Walker, Fok, & Yap, 1989;Channon, Hemsley, 4 & de Silva, 1988;Cooper, Anastasiades, & Fairburn, 1992;Cooper & Fairburn, 1992;Fairburn, Cooper, Cooper, McKenna, & Anastasiades, 1991;Green, Elliman, Rogers, & Welch, 1997;Lovell & Williams, 1997;Schotte, McNally, & Turner, 1990); and treatment trials using``dismantling'' techniques have found that removing the procedures designed to produce cognitive change from CBT has resulted in patients being markedly prone to relapse (Fairburn, Peveler, Jones, Hope & Doll, 1993).…”
Section: Introductionmentioning
confidence: 96%
“…Prospective studies have found overconcern with weight and shape to be predictive of problematic eating behavior (Button, Sonuga-Barke, Davies, & Thompson, 1996;Graber, Brooks-Gunn, Paikoff, & Warren, 1994;Killen et al, 1994Killen et al, , 1996; experimental studies have demonstrated that eating disorder patients selectively attend to weight and shape-related information (Ben-Tovim & Walker, 1991;Ben-Tovim, Walker, Fok, & Yap, 1989;Channon, Hemsley, 4 & de Silva, 1988;Cooper, Anastasiades, & Fairburn, 1992;Cooper & Fairburn, 1992;Fairburn, Cooper, Cooper, McKenna, & Anastasiades, 1991;Green, Elliman, Rogers, & Welch, 1997;Lovell & Williams, 1997;Schotte, McNally, & Turner, 1990); and treatment trials using``dismantling'' techniques have found that removing the procedures designed to produce cognitive change from CBT has resulted in patients being markedly prone to relapse (Fairburn, Peveler, Jones, Hope & Doll, 1993).…”
Section: Introductionmentioning
confidence: 96%
“…Green, Wakeling, Elliman, & Rogers, 1998) and bulimic (e.g. Lovell, Williams & Hill, 1997) women. This bias or selective processing is manifest through slower colour-naming of disorder-relevant compared to neutral information and when compared to non-eating-disordered women.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, both clinical and non-clinical samples with body image disturbances devote more attention to threatening body-related information than controls do (e.g., Cooper and Todd 1997;Davidson and Wright 2002;Fairburn et al 1991;Green et al 1994;Jones-Chesters et al 1998;Lovell et al 1997).…”
mentioning
confidence: 96%